Jumping to conclusion?: A Lévy flight model of decision making [dataset] - Hunsmann, Eva Marie; Voß, Andreas; Radev, Stefan (Universität, 2021)
The diffusion model is one of the most prominent response time models in cognitive psychology. The model describes evidence accumulation as a stoch...
Gesehen am 10.02.2021
Keywords: Forschungsdaten; Datenbank